Extrato de café verde microencapsulado com diferentes agentes e métodos de secagem e sua aplicação em bebida láctea : efeitos sobre características físico-químicas, estabilidade e aspectos sensoriais - Carmo, Laísa Bernabé (2019)
Green coffee is rich in bioactive compounds with antioxidant activity, such as chlorogenic acid, caffeine and trigonellin. These compounds have a beneficial effect in reducing the risk of insulin resistance, cardiovascular diseases, and protectives effects against cancer. The development of products with higher antioxidant content has attracted the interest of the food industry, by adding nutritional value to the products. Furthermore, the incorporation of dietary fibers into food products contributes to the improvement of nutritional aspects. The objective of the present study was to encapsulate the green coffee extract by spray-drying (SD) and freeze-drying (LF) techniques, using two encapsulating agents, incorporate into unfermented dairy beverages and evaluate the effects on characteristics physicochemical, stability of bioactive compounds and sensory aspects. The green coffee extract was obtained by counter-current leaching process. After the microencapsulation of the extracts was performed by spray-drying or freeze-drying, using polydextrose or inulin as encapsulating agent in the ratio 1:2 (v/v). It was elaborated a base formulation of unfermented dairy beverage (control, CT - without green coffee extract) and 4 dairy beverages from the base formulation, but added with extract encapsulated with polydextrose by spray-drying (PD-SD) or freeze-drying (PD-LF) or with extract encapsulated with inulin by spray-drying (IN-SD) or freeze-drying (IN-LF). The extracts encapsulated were characterized as moisture, water activity, pH, hygroscopicity, solubility, total phenolics, antioxidant activity, caffeine content, chlorogenic acid, trigonelline, particle size and structure. It was evaluated the effect of the incorporation of extracts encapsulated in dairy beverages on phenolic content, antioxidant capacity, caffeine, chlorogenic acid and trigonelline stability and acidity over 7 days of storage. The sensorial aspects were analyzed regarding the acceptance and intention to purchase the products. The dry extract by LF with IN showed lower humidity (0.35 g/100g), water activity (0.03) and hygroscopicity (14.93%), in relation to dry extracts using the other conditions. The techniques and encapsulating agents did not present significant differences (p>0.05) in relation to solubility, total phenolics, antioxidant activity, caffeine content and chlorogenic acid. For trigonelin, the IN encapsulated extract presented slightly lower content (4.87 mg/g) than the PD encapsulated extract when the SD was used (p=0.05). The SD particles were spherical in shape, whereas the freeze-drying products showed irregular structures. Compared to CT, the dairy beverages incorporated with the encapsulated extracts had higher total phenolic content (variation 3.05 to 3.42 mg AGE/mL) and higher antioxidant activity, both by ABTS (variation 101.25 to 109.30 µmol Trolox/mL) and by DPPH assay (variation 6.78 to 14.56 µmol Trolox/mL). It was observed that the addition of the encapsulated extracts allowed greater antioxidant activity at the end of 7 days of storage, in relation to CT. The microencapsulation allowed the controlled release of the bioactive compounds in the beverages, in which an increase was observed in the caffeine, chlorogenic acid and trigonelin content during storage. The beverages formulated with the encapsulated extracts presented good acceptance by the consumers, in which the beverage IN-LF presented better acceptance for the attributes global impression and intention of purchase. In summary, the microencapsulation of the green coffee extract showed to be a promising option for the maintenance of bioactive compounds, presenting potential application in the improvement of the health properties of the dairy beverages, in which the extract encapsulated by LF with IN presented more desirable physical characteristics and allowed the formulation of a product with better sensory acceptance.